Framework for examination of software quality characteristics in conflict: A security and usability exemplar. Issue 1 (1st January 2020) - Naqvi, Bilal; Seffah, Ahmed; Abran, Alain
Abstract: Standards and best practices for software quality guide on handling each quality characteristic individually, but not when two or more characteristics come into conflict such as security and usability. The objectives of this paper are twofold: (a) to argue on the importance of handling the conflicts between quality characteristics in general; (b) to formulate a framework for conflict examination of the software quality characteristics, we do so while considering the specific case of security and usability. In line with the objectives, a framework called Pattern-oriented Design Framework (PoDF) was formulated. The PoDF provides a mechanism for identification of the conflicts, modeling the conflicts to illuminate the reason for their occurrence, and eliciting the suitable trade-offs between the conflicting characteristics. The suitable trade-offs are thus documented as design patterns. The patterns can assist developers and designers in handling the conflicts in other but similar context of use. To validate and instantiate the PoDF, two studies were conducted. Usable security patterns discovered as a result of the studies are also presented in the paper.